Arrest, detention, and criminal justice system a study in the context of the constitution of India - Uma Devi, B. (New Delhi ; Oxford : Oxford University Press, 2012)
Fundamental rights enshrined in the Constitution of India protect Indian citizens against the misuse of powers by the state. However, to maintain law and order, the state often disregards this and commits human right violations. Examining the criminal justice system in India, this book focuses interpretations by the Supreme Court of India.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of -- India; Arrest -- India; Constitutional law -- India